2018
DOI: 10.1039/c8cp01353e
|View full text |Cite
|
Sign up to set email alerts
|

Highly negative Poisson's ratio in a flexible two-dimensional tungsten carbide monolayer

Abstract: Auxetic materials have numerous promising engineering applications such as fracture resistance and energy storage due to their negative Poisson's ratios (NPRs). However, compared to materials possessing positive Poisson's ratios (PPRs), auxetic materials are rare. In this paper, by employing first principles calculations, we found a high NPR two-dimensional (2D) material, tungsten carbide (W2C), in the transition metal carbides (MXenes). Our results of the relatively moderate Young's modulus and fracture stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 52 publications
3
24
0
1
Order By: Relevance
“…Similar findings on the effect of monolayer thickness on the elastic properties of the carbide (Ti n+1 C n ) and nitride-based (Ti n+1 N n ) MXenes, by DFT calculations, were reported in another study [ 53 ]. It was shown that increasing the monolayer thickness decreases Young’s moduli of MXenes.…”
Section: Mechanical Properties Of Self-standing Mxenessupporting
confidence: 87%
See 4 more Smart Citations
“…Similar findings on the effect of monolayer thickness on the elastic properties of the carbide (Ti n+1 C n ) and nitride-based (Ti n+1 N n ) MXenes, by DFT calculations, were reported in another study [ 53 ]. It was shown that increasing the monolayer thickness decreases Young’s moduli of MXenes.…”
Section: Mechanical Properties Of Self-standing Mxenessupporting
confidence: 87%
“…Another study [ 53 ] predicted enhanced elastic properties of a 2D Tungsten Carbide (W 2 C) monolayer by DFT calculations. The calculated c 11 of 781.9 GPa indicated that W 2 C is mechanically stable as it satisfies the 2D materials criteria for mechanical stability [ 36 ].…”
Section: Mechanical Properties Of Self-standing Mxenesmentioning
confidence: 99%
See 3 more Smart Citations